Exploring the Impact of Transformational Leadership, Training, and Employee Engagement on Restaurant Employee Performance - Setijadi, Veronica; K, Tin Agustina; Widodo, Teguh (Journal of Educational Management Research, 2025)
This study aims to analyze the influence of transformational leadership, training programs, and employee engagement on employee performance. A quantitative approach was used in this study, with a sample of 72 employees from a restaurant in Malang selected through purposive sampling. Data were analyzed using multiple linear regression methods. The main results of this study indicate that transformational leadership and employee engagement have a positive and significant influence on employee performance. In contrast, training programs do not show a significant effect. The practical implication of these findings is that performance improvements can be more effectively achieved through an inspirational leadership style and employee emotional engagement. Furthermore, there is a need to re-evaluate the effectiveness of existing training programs. A limitation of this study is that the sample coverage is limited to one company, so generalizing the results to a broader context requires caution.